Diagnostic and therapeutic role of bronchoscopy in suspected cases of foreign bodies in tracheobronchial tree in pediatric age group - Ambani, Kirti P.; Chavda, Amit B.; Patel, Urvish D.; Mulani, Ajay M.; Shah, Shaili S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Aim and objectives were to review the importance and benefits of bronchoscopy in suspected foreign body aspiration in tracheobronchial tree, prompt diagnosis and early management, and correlation between clinical and bronchoscopic findings. Methods: A retrospective study was conducted. Total 50 pediatric patients were enrolled in our study who were giving strong history of foreign body aspiration with sudden respiratory symptoms. Chest X-ray PA view was performed in all the patients. All the bronchoscopy done under general anesthesia. Results: In our study, children between 6 months to 3 years of age are the commonest victims, males are more affected than females. Classic triad of unilateral wheeze, coughing, and ipsilateral reduced air entry-is observed in less than 50% of cases. Conclusions: Bronchoscopy is essential in all cases of bronchial foreign body known or suspected and rigid bronchoscopy has proven over time to be safest and most efficacious to therapy. Although X-ray examination is essential for diagnosis and management, CT thorax with virtual bronchoscopy is advisable before bronchoscopy procedure in suspected cases (if general condition permits), it gives better idea about exact location, nature and type of foreign body.